The Students’ Perception toward TOEFL Test (a Study on Cognitive Component) - Rahmi, Silfia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The current study aims at investigating the students perception on cognitive component toward TOEFL test at IAIN Batusangkar.  This research used a mixed method. The participants of this research were 373 (three hundred and seventy three) students who graduated at IAIN Batusangkar in July 2020 for getting quantitative data. Meanwhile, there were 37 (thirty seven) students participated on getting qualitative data. The instruments used to collect the data was questionnaire together with interview guide. The data obtained from the questionnaire were analyzed based on formula suggested by Heaton and Djemari and Arikunto. Meanwhile, the data got from interview guide were analyzed based on the theory suggested by Miles and Huberman. The research findings indicate that most of students have strongly positive perception on cognitive component toward TOEFL test at IAIN Batuangkar. It was 76,47 %. Then, there were two common reasons why the students have positive perception on cognitive component toward TOEFL test. Thus, it can be concluded that the regulation of providing TOEFL test is useful and be good to be continued by UPB since there was positive opinion of students’ toward TOEFL test. However, it will be required to give the training to help them to get the better score since the low ability they have. A good opinion is only one of the factors to get the better score.